SUPPORT MECHANISMS OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP AND THE RESULTS OF ITS IMPLEMENTATION - Shakirova Gulbakhor Sharipjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article presents ideas and considerations on the mechanisms of support for small business and private entrepreneurship and the results of its implementation, as well as the role of the state in forming a system of rules for the activities of scientific and technical market entities and monitoring their implementation through the formation of a favorable institutional environment and innovative infrastructure.